Guaiacol-polyvinyl alcohol / chitosan composite film, preparation method thereof and application of guaiacol-polyvinyl alcohol / chitosan composite film in fruit preservation
By developing the guaiacin-polyvinyl alcohol/chitosan composite membrane, the problem of fruit rot and deterioration in the existing fruit preservation technology has been solved, and a longer shelf life and better fruit quality has been achieved.
Patent Information
- Application Number
- CN202510203347.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fruit preservation technology is difficult to effectively prevent fruit from rotting and deteriorating, and the single packaging material has defects in mechanical properties, oxidation resistance and antibacterial effects.
A guaifene-polyvinyl alcohol/chitosan composite film was developed, and a composite film with excellent mechanical properties, antioxidant and antibacterial effects was prepared by mixing chitosan, polyvinyl alcohol and guaifene nanoemulsion.
The composite membrane significantly improves the shelf life of fruits, inhibits the decline in freshness, delays the decomposition of titable acids, soluble solids and ascorbic acid, and effectively prevents fruit from rotting and spoiling.
Smart Images

Figure CN119899482A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fresh-keeping, and in particular relates to a guaiacene-polyvinyl alcohol / chitosan composite film, a preparation method thereof and application thereof in fruit fresh-keeping. Background Art
[0002] Post-harvest loss of fruits and vegetables is a technical problem. There are many reasons for post-harvest loss of fruits and vegetables, among which the loss of fruits and vegetables caused by pathogens and spoilage bacteria is the most common and serious. Therefore, ensuring the quality of fruits and vegetables after harvest, extending their shelf life, preventing them from rotting and deteriorating, and reducing losses are urgent issues to be solved in the preservation of fruits and vegetables after harvest.
[0003] The development of fruit preservation technology is to extend the shelf life of fruits, maintain their freshness, nutritional value and taste, and reduce losses during transportation and storage. With the advancement of food technology and the increasing demand of consumers for healthy food, fruit preservation technology has evolved from traditional physical and chemical methods to more advanced and environmentally friendly biotechnology and nanotechnology.
[0004] Chitosan is a unique polysaccharide isolated from crustacean waste, which has shown wide applications in food preservation. However, pure chitosan has weak mechanical properties, can only be dissolved in acidic media, and loses its antimicrobial activity at pH>6.5. In addition, single packaging materials are easily affected by their own structure and have certain defects in gas barrier properties, water resistance, transparency and strength. Therefore, it is of great social value to develop a composite film matrix with better mechanical properties to improve fruit preservation technology. Summary of the invention
[0005] The invention provides a fresh-keeping film, which is a guaiacene-polyvinyl alcohol / chitosan composite film containing polyvinyl alcohol, chitosan and guaiacene.
[0006] The above-mentioned guaiacene-polyvinyl alcohol / chitosan composite film is prepared by the following method:
[0007] Chitosan, polyvinyl alcohol and glycerol are added to glacial acetic acid, and stirred in a water bath until the membrane substrate is dissolved to obtain a membrane liquid; after the membrane liquid is cooled to room temperature, guaiacene nanoemulsion is added, stirred evenly, and allowed to stand to defoam to obtain a mixed membrane liquid; then the mixed membrane liquid is dried, and the film is removed after cooling to obtain a guaiacene-polyvinyl alcohol / chitosan composite membrane.
[0008] In the above preparation method, each material is selected from the following parts:
[0009] 1-2 parts of chitosan, 1-3 parts of polyvinyl alcohol, 1-3 parts of glycerol, 1-2 parts of glacial acetic acid, 2-4 parts of guaiacene nanoemulsion;
[0010] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0011] In a specific embodiment, each material is selected from the following parts:
[0012] 1 part of chitosan, 2 parts of polyvinyl alcohol, 2 parts of glycerol, 1 part of glacial acetic acid, 3 parts of guaiacene nanoemulsion;
[0013] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0014] In the above preparation method, the temperature of the water bath stirring is selected from 50 to 70°C, preferably 60°C.
[0015] In the above preparation method, the guaiacene nanoemulsion is prepared by the following method:
[0016] Guaiene and an emulsifier are added into water, stirred evenly, and then sheared at a high speed to obtain a crude emulsion; the crude emulsion is ultrasonically emulsified under ice bath conditions to obtain a guaiacene nanoemulsion.
[0017] In the above-mentioned method for preparing the guaiacene nanoemulsion, each material is selected from the following weights:
[0018] 1-3 parts of guaiacene, 1-5 parts of emulsifier, 92-98 parts of water;
[0019] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0020] In a specific embodiment, each material is selected from the following parts:
[0021] 2 parts of guaiacene, 2 parts of emulsifier, 96 parts of water;
[0022] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0023] In the above method for preparing the guaiacene nanoemulsion, the stirring condition is selected from: stirring at 250-350 rpm for 15-25 min; preferably: stirring at 300 rpm for 20 min.
[0024] In the above method for preparing guaiacene nanoemulsion, the high-speed shearing is selected from: high-speed shearing at 10000-11000 rpm for 2-3 min; preferably: high-speed shearing at 10000 rpm for 2 min.
[0025] In the above method for preparing guaiacene nanoemulsion, the ultrasonic power of the ultrasonic emulsification is selected from 300 to 400 W, preferably 350 W.
[0026] The present invention provides the use of the guaiacene-polyvinyl alcohol / chitosan composite film or the guaiacene-polyvinyl alcohol / chitosan composite film prepared by the method in preserving fruits and vegetables.
[0027] The beneficial effects of the present invention are:
[0028] The invention optimizes the formula and adds guaiacene nanoemulsion into the polyvinyl alcohol / chitosan composite film, thereby improving the mechanical properties, antioxidant properties, antibacterial effect, water vapor permeability and appearance of the composite film, being able to prolong the shelf life of the Nanguo pear, inhibit the decline in the freshness of the Nanguo pear, and delay the decomposition of the titratable acid, soluble solids and ascorbic acid of the Nanguo pear, playing an important role in maintaining the quality of the fruit, and thus having important application value and prospect in the field of fruit and vegetable preservation. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is the opacity of films of different materials;
[0030] Figure 2 is the diameter of the inhibition zone of Aspergillus niger;
[0031] Figure 3 is the antioxidant activity of each film;
[0032] Figure 4 Effect of composite film on the decay of Nanguo pear inoculated with Aspergillus niger
[0033] Figure 5 This is the cross-sectional view of Nanguo pear after 7 days of composite film treatment;
[0034] Figure 6 is the weight loss rate change of Nanguo pear;
[0035] Figure 7 is the change of the diameter of the lesion of Nanguo pear;
[0036] Figure 8 The change of soluble solid content of Nanguo pear;
[0037] Fig. 9 The titratable acid content of Nanguo pear varies; DETAILED DESCRIPTION
[0038] The materials used in the present invention are as follows:
[0039] Guaiene (Guaiene) (>99.0%), Aladdin); polyvinyl alcohol (PVA), Shandong Keyuan Biochemical Co., Ltd.; chitosan (CS) (MW=300000), Shanghai MacLean Biochemical Technology Co., Ltd.; glycerol (analytical alcohol AR), Sinopharm Chemical Reagent Co., Ltd.; Tween 80, MacLean; anhydrous ethanol (analytical alcohol AR), Tianjin Fuyu Fine Chemical Co., Ltd.
[0040] Other materials used in the present invention, unless otherwise stated, can be obtained through commercial channels. Other terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The present invention is further described in detail below in conjunction with specific examples and with reference to data. The following examples are only intended to illustrate the present invention, and are not intended to limit the scope of the present invention in any way.
[0041] Example 1
[0042] The guaiacene nanoemulsion was prepared by the following steps:
[0043] Guaiene was used as the oil phase and Tween 80 was used as the emulsifier. 2 mL of guaiacene and 2 mL of Tween 80 were added to 96 mL of deionized water, and magnetically stirred at 300 rpm for 20 min at room temperature, and then sheared at 10000 rpm for 2 min using a high-speed shearing machine to obtain a crude emulsion, which was then ultrasonically emulsified for 15 min in an ice bath using an ultrasonic cell disruptor (350 W) to obtain a guaiacene nanoemulsion (GNE).
[0044] 1. Characterization and stability of guaiacene nanoemulsion
[0045] 1. Determination of particle size, PDI and Zeta potential
[0046] The average droplet size and particle size distribution were determined by dynamic light scattering (DLS) at a scattering angle of 173° using a nanoparticle sizer. To avoid multiple scattering effects, the guaiacene nanoemulsion was diluted 100 times with deionized water before measurement. The measurements were performed at 25°C after 90 s of equilibrium, and each sample was scanned three times. Then, the average droplet size and polydispersity index (PDI) were reported to represent the average particle size, PDI, and potential of each sample, respectively.
[0047] Average particle size, PDI, zeta potential and particle size distribution are very important indicators of nanoemulsions, which can describe the size, stability, uniformity and dispersibility of nanoemulsions. The larger the zeta potential, the greater the mutual repulsion between particles and the better the stability of the dispersed system. The guaiacene nanoemulsion was measured using a laser particle size / potential analyzer. The experimental results obtained are shown in Table 1.
[0048] Table 1 Basic properties of guaiacene nanoemulsion
[0049] Emulsifier addition amount (v / v) Particle size (nm) PDI Potential (mV) 2% 99.40±0.62 0.27±0.004 -14.80±0.44
[0050] As shown in Table 1, the average particle size of the guaiacene nanoemulsion is 99.40 ± 0.62 nm, the PDI is 0.27 ± 0.004, and the zeta potential is -14.80 ± 0.44 mV. The results show that the system is stable, the average particle size of GNE is small, the droplets are well dispersed, the size is uniform, and there is basically no aggregation phenomenon.
[0051] Example 2
[0052] The guaiacene-polyvinyl alcohol / chitosan composite film was prepared in the following steps:
[0053] 1 g chitosan, 2 g polyvinyl alcohol and 2 mL glycerol were added to 1 mL glacial acetic acid, and magnetically stirred for 60 min in a 60 ° C water bath until the membrane substrate was completely dissolved and mixed thoroughly; after the membrane liquid was cooled to room temperature, 3 mL guaiacene nanoemulsion was added to the membrane liquid, and then stirred at low speed and room temperature for 30 min, and allowed to stand to defoam; then the mixed membrane liquid was poured on a culture dish, placed in a 50 ° C oven to dry for 20 h, and the film was removed after cooling to obtain a guaiacene-polyvinyl alcohol / chitosan composite film.
[0054] 2. Properties of guaiacene-polyvinyl alcohol / chitosan composite films
[0055] 1. Opacity analysis
[0056] The film sample to be tested was cut into a rectangle of 10 mm × 40 mm and placed on one side of the cuvette. The absorbance of the composite film at 600 nm was measured using an ultraviolet spectrophotometer. The opacity of the composite film was calculated using the following formula:
[0057] Opacity=A 600 / T;
[0058] Where Opacity is the film opacity, mm -1 , T is the thickness of the film, in mm.
[0059] Test results such as Figure 1 As shown:
[0060] Compounding PVA with CS did not substantially change the opacity of the film, while the opacity of the composite film increased dramatically after the addition of Guaiene. The composite film with the addition of GNE had a lower opacity, which may be due to the fact that when guaiacene is added in the form of a nanoemulsion, its particle size is usually small and evenly dispersed. In contrast, the direct addition of guaiacene may result in particle aggregation or uneven distribution. Smaller nanoemulsion particles can scatter light better and reduce light transmission, resulting in lower opacity.
[0061] 2. Determination of antibacterial activity
[0062] Aspergillus niger is widely distributed in soil, air, and plant products around the world, causing spoilage of fruits, vegetables, feed, and grain. In this study, the activity of PVS-CS, PVA-CS-Guaiene, and PVA-CS-GNE against A. niger was evaluated based on in vitro antibacterial experiments. A. niger (ATCC 16404) strain was selected for the experiment.
[0063] Using Aspergillus niger as the indicator bacteria, the double-layer plate method was used to determine the inhibitory effect of the composite film solution on Aspergillus niger. First, pour 15 mL of PDA, and then pour another 15 mL of PDA after coagulation. Coat 1×10 6 500 μL of spore solution with a CFU / mL was added, and after complete absorption, a hole (6 mm) was punched, and 500 μL of the prepared membrane solution was added. The mixture was cultured at 37°C for 48 h, and the diameter (mm) of the inhibition zone was measured.
[0064] Test results such as Figure 2 As shown:
[0065] PVS-CS, PVA-CS-Guaiene, and PVA-CS-GNE films showed different inhibition diameters on A. niger, which were 12.59 mm, 14.98 mm, and 19.77 mm, respectively. It is worth noting that PVS-CS-GNE showed the highest antibacterial activity. The experimental results showed that the PVS-CS-GNE composite film had a good inhibitory effect on A. niger.
[0066] 3. Antioxidant properties
[0067] (1) DPPH free radical scavenging rate
[0068] Take 3mL of DPPH free radical solution (0.2mM, dissolved in anhydrous ethanol) and mix thoroughly with 20mg of different composite membrane sample solutions, place in the dark for 30min, and use the ethanol solution without sample as blank to measure the absorbance at 517nm. The scavenging activity of the sample on DPPH free radicals is calculated according to the following formula.
[0069]
[0070] Wherein: DPPH is the free radical scavenging rate of the membrane, %; A1 is the absorbance value of the control solution; A2 is the absorbance value of the membrane solution to be tested.
[0071] (2) ABTS free radical scavenging rate
[0072] 7mmol / L ABTS and 2.45mmol / L K2S8O2 were reacted at room temperature in the dark for 16h, and diluted with phosphate buffer (pH=7.4) to an absorbance of (0.7±0.003) at 734nm to obtain ABTS working solution. 0.3mL of film sample solution and 75% ethanol were mixed with 3mL of ABTS solution respectively, and reacted at room temperature in the dark for 10min. The absorbance at 734nm was read. The ABTS cation radical scavenging rate was calculated according to the following formula.
[0073]
[0074] Wherein: ABTS is the free radical scavenging rate of the membrane, %; A1 is the absorbance value of the control solution; A2 is the absorbance value of the membrane solution to be tested.
[0075] Test results such as Figure 3 As shown:
[0076] The antioxidant activity of the film is expressed by the scavenging rate of DPPH free radicals and ABTS cation free radicals. The greater the scavenging rate of DPPH free radicals and ABTS cation free radicals, the stronger the antioxidant activity. Figure 3 It can be seen that with the addition of guaiacene and guaiacene nanoemulsion, the scavenging rates of DPPH radicals and ABTS cation radicals showed a significant upward trend. When guaiacene nanoemulsion was added, the scavenging rates of DPPH radicals and ABTS cation radicals reached 79.55% and 84.39%, respectively, indicating that the PVA-CS-GNE composite film has good antioxidant properties.
[0077] 4. Mechanical properties test
[0078] The film was cut into 1cm×5cm strips, and the thickness tester was used to randomly measure 5 locations of the film and take the average value. Then, the tensile strength (TS), elongation at break (EAB) and Young's modulus (EM) of the film were measured using an electronic universal material testing machine. Three copies of the film of each formulation were used as parallel samples, and the average value of the mechanical properties of the five groups of parallel films of each formulation was recorded. The initial length between the two clamps and the tensile speed during the measurement were 50mm and 0.5mm / s, respectively.
[0079] The calculation formula is as follows:
[0080]
[0081] Where: F is the axial tension, N; M is the film thickness, mm; L is the film width, mm.
[0082]
[0083] Where: H0 is the initial separation distance, H is the distance when the film breaks.
[0084] The test results are shown in Table 2:
[0085] Table 2 Mechanical properties of films
[0086]
[0087] The thickness and color properties of food packaging films have a significant impact on the overall appearance and consumer acceptance. As shown in Table 2, after adding GNE to the PVA-CS composite film, the thickness of the film increased from 0.107 ± 0.005 mm to 0.139 ± 0.002 mm, which is due to the addition of more solid content in the polymer matrix.
[0088] Mechanical properties are key parameters of packaging films, which will affect the use range and durability of the film. As shown in Table 2, the mechanical properties of the composite film prepared by PVA and CS are better than those of the film prepared by a single material. This is because PVA and CS have good compatibility, and hydrogen bonds are formed between the -OH group of PVA and the -NH2 group of CS, forming a physical network structure with a certain tensile strength and a high elongation at break. Adding Guaiene and GNE to the composite film can further optimize the mechanical properties of the film, among which PVA-CS-GNE has the best mechanical properties.
[0089] Application Example 1 Application of composite film in the preservation of Nanguo pear
[0090] 1. Storage and processing of Nanguo pear samples
[0091] Select pears of similar size, uniform maturity, free of pests and diseases, and mechanical damage, rinse with tap water, and dry for later use. Place the pears in trays, with 3 pears per tray, and then use the tip of a sterilizing spray gun to make an inoculation hole of about 2 mm in diameter and 4 mm deep in the equatorial area of the fruit. Inject 10 6CFU / mL Aspergillus niger spore suspension. Covered with different films PE (commercial films commonly used in food), PVA-CS, PVA-CS-Guaiene, PVA-CS-GNE, each Nanguo pear sample was stored at room temperature (25°C, 50% relative humidity), and its appearance changes during storage were observed. The changes in the diameter of the lesions every day and the changes in the depth of the lesions on the last day were recorded.
[0092] Test results such as Figure 4 and Figure 5 As shown:
[0093] The diameter of the fruit lesions gradually increased over time, and the PVA-CS-GNE composite film treatment significantly reduced the lesion diameter. In addition, it can be seen that the lesion depth on the last day of the PVA-CS-GNE composite film was significantly lower than that of the other groups, indicating that the PVA-CS-GNE composite film can effectively reduce the decay and deterioration of Nanguo pear.
[0094] 2. Determination of weight loss rate
[0095] In harvested fresh vegetables and fruits, weight loss, together with water loss due to respiration, can seriously affect their quality and appearance.
[0096] Daily weight loss was determined by weighing the fruit at the same time of day using an analytical balance and expressed as a percentage of the initial weight.
[0097]
[0098] Where W0 is the initial weight of Nanguo pear, g; W t is the weight after storage time, g.
[0099] Test results such as Figure 6 As shown:
[0100] The weight loss rate of Nanguo pear after being treated with different films is as follows Figure 6 As shown. With the extension of storage time, the weight loss rate of the fruit gradually increased, while the PVA-CS-GNE composite film significantly reduced the weight loss of the fruit, but the weight loss rate was higher than that of the PE film treatment group. The reason is that the composite film has a certain air permeability, while the PE film is not air permeable, and water vapor cannot escape, so the weight loss rate is low. Although the weight loss rate of the PVA-CS-GNE composite film is higher than that of PE, it has better air permeability and inhibits the growth of mold, so the composite film can better preserve freshness.
[0101] 3. Determination of lesion diameter
[0102] Use the tip of a sterilized spray gun to make an inoculation hole about 2 mm in diameter and 4 mm deep in the equatorial area of the fruit. Inject 10 6 CFU / mL Aspergillus niger spore suspension. Covered with different films PE, PVA-CS, PVA-CS-Guaiene, PVA-CS-GNE, each Nanguo pear sample was stored at room temperature (25°C, 50% relative humidity) for 7 days and the changes in the diameter of the lesions were measured every day.
[0103] Test results such as Figure 7 As shown:
[0104] The diameter of the fruit lesions will continue to increase with time. The rot rate of the commercially available PE film group increased the fastest, followed by the PVA-CS group, and the diameter of the lesions of the groups with added Guaiene and GNE increased slowly. When the storage time reached 7 days, the lesions of the PE group were the largest, reaching 3.33cm in diameter. The lesion diameter of the PVA-CS group without Guaiene and GNE was also at a high level, and the smallest lesion was the PVA-CS-GNE group, which was only 1.85cm, indicating that the PVA-CS-GNE composite film significantly inhibited the infection of Aspergillus niger.
[0105] 4. Determination of soluble solids
[0106] During storage, starch and other substances in the fruit will decompose into small molecular sugars, increasing the sugar content of the fruit. A certain amount of pulp was weighed, ground, juiced and filtered. After processing, the soluble solids in the Nanguo pear pulp were measured using a digital Abbe refractometer.
[0107] Test results such as Figure 8 As shown:
[0108] Changes of soluble solids in Nanguo pear Figure 8 As shown. The soluble solids content showed a decreasing trend during storage. The decrease in soluble solids content may be due to respiration, which leads to the consumption of sugar and other nutrients. Compared with other groups, the consumption of soluble solids in the PVA-CS-GNE composite film treatment group was significantly reduced, indicating that the PVA-CS-GNE composite film treatment group can effectively inhibit the physiological activities of fruits during storage and delay the decay process.
[0109] 5. Determination of titratable acid content
[0110] Titratable acid content is an important indicator affecting the flavor quality of fruits. Changes in acidity are significantly affected by metabolic rate, especially respiration rate. Titratable acid in fruits is continuously consumed or converted into sugar for cell metabolism during storage.
[0111] Weigh 1g of Nanguo pear sample and grind it in a mortar, transfer it to a 100mL volumetric flask, rinse the grind with distilled water, transfer it to the volumetric flask, let it stand at room temperature for 30 minutes after volume adjustment, and filter. Prepare 0.01mol / L NaOH standard solution in advance and calibrate it. Take 20mL of filtrate, add phenolphthalein, and titrate with standard NaOH solution until the filtrate is just slightly red, and keep it without fading for 30s, and record the volume of NaOH consumed. Each group of titrations is measured three times and the average value is taken. The titratable acid content in Nanguo pear is calculated according to the following formula:
[0112]
[0113] Where: V0 is the volume of NaOH solution consumed in titrating distilled water, mL; V is the total volume of sample extract, mL; V s is the volume of the filtrate taken during titration, mL; V1 is the volume of NaOH solution consumed in titrating the filtrate, mL; m is the sample mass, g; f is 0.067, g / mmol.
[0114] Test results such as Fig. 9 As shown:
[0115] Effects of different treatments on titratable acid content of Nanguo pear Fig. 9 .Depend on Fig. 9 It can be seen that the titratable acid content showed a downward trend with the extension of storage time, and the titratable acid content in each composite film treatment group was significantly higher than that in the control group (P < 0.05). After 7 days of storage, the titratable acid content of the fruit in the PE group was the lowest, which was (0.2714 ± 0.017)%, while the titratable acid content of the PVA-CS-GNE treatment group was the highest, which was (0.3607 ± 0.001)%. Therefore, PVA-CS-GNE treatment can effectively slow down the decrease rate of the titratable acid content in the fruit.
[0116] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A guaiacene-polyvinyl alcohol / chitosan composite film for preservation, characterized in that: Contains polyvinyl alcohol, chitosan and guaiacene.
2. The guaiacene-polyvinyl alcohol / chitosan composite film according to claim 1, characterized in that: The guaiacene-polyvinyl alcohol / chitosan composite film is prepared by the following method: Chitosan, polyvinyl alcohol and glycerol are added to glacial acetic acid, and stirred in a water bath until the membrane substrate is dissolved to obtain a membrane liquid; after the membrane liquid is cooled to room temperature, guaiacene nanoemulsion is added, stirred evenly, and allowed to stand to defoam to obtain a mixed membrane liquid; then the mixed membrane liquid is dried, and the film is removed after cooling to obtain a guaiacene-polyvinyl alcohol / chitosan composite membrane.
3. The guaiacene-polyvinyl alcohol / chitosan composite film according to claim 2, characterized in that: The ingredients are selected from the following quantities: 1-2 parts of chitosan, 1-3 parts of polyvinyl alcohol, 1-3 parts of glycerol, 1-2 parts of glacial acetic acid, and 2-4 parts of guaiacene nanoemulsion.
4. The guaiacene-polyvinyl alcohol / chitosan composite film according to claim 2, characterized in that: The temperature of the water bath stirring is selected from 50 to 70°C.
5. The guaiacene-polyvinyl alcohol / chitosan composite film according to claim 2, characterized in that: The guaiacene nanoemulsion is prepared by the following method: Guaiene and an emulsifier are added into water, stirred evenly, and then sheared at a high speed to obtain a crude emulsion; the crude emulsion is ultrasonically emulsified under ice bath conditions to obtain a guaiacene nanoemulsion.
6. The guaiacene-polyvinyl alcohol / chitosan composite film according to claim 5, characterized in that: The ingredients are selected from the following quantities: 1-3 parts of guaiacene, 1-5 parts of emulsifier, and 92-98 parts of water.
7. The guaiacene-polyvinyl alcohol / chitosan composite film according to claim 5, characterized in that: The stirring condition is selected from: stirring at 250-350 rpm for 15-25 min.
8. The guaiacene-polyvinyl alcohol / chitosan composite film according to claim 5, characterized in that: The high-speed shearing is selected from: high-speed shearing at 10000-11000 rpm for 2-3 min.
9. The guaiacene-polyvinyl alcohol / chitosan composite film according to claim 5, characterized in that: The ultrasonic power of the ultrasonic emulsification is selected from 300 to 400W.
10. Use of the guaiacene-polyvinyl alcohol / chitosan composite film according to any one of claims 1 to 9 in preserving fruits and vegetables.
Citation Information
Cited By
Tea tree essential oil-thyme essential oil-chitosan composite membrane as well as preparation method and application thereof
CN120590657A
Tea tree oil-thyme oil-chitosan composite membrane, its preparation method and application
CN120590657B